AWAS: STUDI KAUSAL-KOMPARATIF - Soetarlinah Sukadji (Buletin Psikologi, 1997)
Fred N. Kerlinger (1986)  dalam bukunya Foundation of behavioral research (p.348) mendahului ulasannya sebagai berikut: "Among prevalent fallacies, on of the most dangerous to science is thay known as post hoc, ergo propter hoc: after this, therefore caused by this."